Esporos de fungos e forrageiras: construindo alianças edáficas em solos do cerrado-pantanal - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The Cerrado ecosystems are characterized by abiotic conditions that are adverse to plant growth, such as low phosphorus levels and a seasonal water regime. In these challenging environments, plants depend on interactions with soil microorganisms to overcome these limitations. Arbuscular mycorrhizal fungi (AMF) are important because they promote plant growth by establishing symbiotic associations with plant roots, increasing the efficiency of absorbing essential nutrients such as phosphorus, nitrogen, and other minerals that are scarce in tropical soils. These fungi form a network of hyphae that extends into the soil beyond the roots, expanding the area of soil exploration, which is especially beneficial for the uptake of low-mobility nutrients. In addition, AMF assist in water absorption, making plants more resilient during periods of drought. The high biodiversity of AMF in the Cerrado presents great potential for the development of mycorrhizal inoculants, a promising technology to enhance plant nutritional efficiency and reduce dependence on chemical inputs. The bioprospecting of native AMF species in the Cerrado emerges as an important strategy for promoting sustainable agriculture, especially in degraded soils. This work aims to review the diversity, ecological functions, and potential sustainable agricultural applications of mycorrhizae in the Cerrado.
Fungal spores and forage: building edaphic alliances in cerrado-pantanal soils
Keywords: Fungos micorrízicos arbusculares; Agricultura sustentável; Bioprospecção; Forragicultura; Arbuscular mycorrhizal fungi; Sustainable agriculture; Bioprospecting; Forage farming; CIENCIAS AGRARIAS